Queer penalities: the criminal justice paradigm in lesbian and gay anti-violence politics - Russell, Emma K. (Critical criminology, 2017)
Building upon the renewed attention to the ways in which criminology may be ‘queered’ (or not), this article explores how a criminal justice paradigm has influenced lesbian and gay politics through an investigation of anti-homophobic research and lobbying focused on violence and harassment. It asks: What place does criminal justice occupy within sexual politics? Using the Australian state of Victoria as a case study, the article examines how the lesbian and gay anti-violence movement has utilized criminal justice theories, methodologies and approaches to explain and attempt to remedy ‘homophobic hate’. It provides three inter-connected examples of the permeation of criminal justice logics: (1) the victimization survey method, (2) the focus on police reform, and (3) elements of a punitive public discourse surrounding homophobic hate crime. These examples are nevertheless complicated by the persistence of institutionalized violence and state failure to ‘protect’ lesbian, gay, bisexual and transgender (LGBT) lives. These discursive practices contribute to ‘queer penalities’, a term used to describe the ways in which lesbian and gay movements shape and contest the social meaning of terms such as ‘crime’, victimization and punishment.